COMBINED ADMINISTRATION OF SPONDIAS MOMBIN AND FICUS EXASPERATA LEAF EXTRACTS STALL INDOMETHACIN-MEDIATED GASTRIC MUCOSAL ONSLAUGHT IN RATS. - Sabiu, Saheed; Olarewaju, Sulyman Abdulhakeem; Taofeeq, Garuba; Olatunde, Sunmonu Taofik; Alanamu, Abdulrahaman Abdullahi (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Despite the rapidly changing concept of gastric ulcer management from conventional vagotomy, H2 receptor antagonists and antacids to proton pump inhibitors, gastrointestinal toxicity remains an impediment to their application in clinical practice. Combined administration of two or more plant extracts with therapeutic efficacy may proffer solution to this menace. This study investigated the combined gastroprotective effects of Spondias mombin and Ficus exasperata leaf extracts against indomethacin-induced gastric ulcer in rats. Materials and Methods: Thirty rats were randomized into six groups of five animals each and ulceration was induced by a single oral administration of indomethacin (30 mg/kg body weight). Ulcerated rats were orally administered with Spondias mombin, Ficus exasperata at 200 mg/kg body weight and esomeprazole (a reference drug) at a dose of 20 mg/kg body weight once daily for 21 days after ulcer induction. At the end of the experiment, gastric secretions and antioxidant parameters were evaluated. Results: We observed that the significantly increased (P < 0.05) ulcer index, gastric acidity, malondialdehyde level and pepsin activity were markedly reduced following co-administration of S. mombin and F. exasperata. The extracts also effectively attenuated the reduced activities of superoxide dismutase and catalase as well as pH, mucin content and reduced glutathione level in the ulcerated rats. Discussion and Conclusion: These findings are indicative of gastroprotective and antioxidative attributes of the two extracts which is also evident in the % protective index value obtained. The available evidences in this study suggest that the complementary effects of S. mombin and F. exasperata proved to be capable of ameliorating indomethacin-mediated gastric ulceration and the probable mechanisms are via antioxidative and proton pump inhibition.